ANALISIS PENGELOLAAN WISATAWAN MANCANEGARA DI DESTINASI PARIWISATA NUSA LEMBONGAN KABUPATEN KLUNGKUNG BALI - Dewa Ayu Made Lily Dianasari; Ni Made Tirtawati; Hanugerah Kristiono Liestiandre; Ida Bagus Putra Negarayana; I Gede Gian Saputra (JURNAL KEPARIWISATAAN, 2020)
The purpose of this study is to determine the perceptions of tourists towards Nusa Lembongan as a destination and the management of tourists in Nusa Lembongan. The determination of the sample in this study was to obtain data on the characteristics of tourists visiting Nusa Lembongan with 103 respondents using qualitative analysis techniques. The results of the study are tourists’ perceptions of Nusa Lembongan from indicators of awareness 58.43% (agree), attractiveness 65.2% (agree), availability 63.08% (agree), accessibility 62.95% (agree), destination appreciation (66.3%), assurance 58.2%, activity 45.6%, appearance 58.3% (agree).